2022
DOI: 10.1186/s12887-022-03588-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimum dietary diversity and associated factors among lactating mothers in Haryana, India: a community based cross-sectional study

Abstract: Introduction Food adequacy and dietary quality in the lactation period are fundamental for maternal and child health. Lactating mothers are vulnerable to malnutrition because of increased physiological demand, monotonous diet, lactogenesis process, and increased nutrient requirements. The micronutrient adequacy especially among women is not ensured in Indian diet. The dual course of gender bias and poverty, along with lack of knowledge about diet quality are significant impediments in maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Low micronutrient intake, accompanied by poor consumption of essential fatty acids such as omega 6 and omega 3 fatty acids, may lead to an increased risk of poor pregnancy outcomes such as low birth weight, stillbirth, and stunting, among others. The findings from the study conducted by Shumayla et al (2022) were in contrast to the findings from this study, where high nutritional knowledge was a factor that influenced the high consumption of diverse groups of foods. Another study suggested that seasonality may be a factor that influences the consumption of different groups (Custodio et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Low micronutrient intake, accompanied by poor consumption of essential fatty acids such as omega 6 and omega 3 fatty acids, may lead to an increased risk of poor pregnancy outcomes such as low birth weight, stillbirth, and stunting, among others. The findings from the study conducted by Shumayla et al (2022) were in contrast to the findings from this study, where high nutritional knowledge was a factor that influenced the high consumption of diverse groups of foods. Another study suggested that seasonality may be a factor that influences the consumption of different groups (Custodio et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, this is the rst study in the select study sites. A study conducted in Haryana by (21) reported more than three-fourth of the lactating mothers consuming a minimum diversi ed diet. Compared to this study, the high prevalence of dietary diversity can be attributed to the fact that the state of Haryana is predominantly an agricultural state, resulting in relatively better dietary diversity (22).…”
Section: Discussionmentioning
confidence: 99%
“…The K- and P-Scores iron were not related. Also, studies in Africa [ 33 , 35 , 40 , 43 , 47 , 62 , 63 , 64 ] and Asia [ 33 , 65 , 66 , 67 ] and a review of studies in mainly industrialized countries [ 68 ] mostly found positive, often weak associations of nutritional knowledge/having received nutrition information with dietary intake, dietary diversity, food variety, or consumption of animal foods among (pregnant) mothers, caregivers, and the community.…”
Section: Discussionmentioning
confidence: 99%